Accurate prediction of X-ray pulse properties from a free-electron laser using machine learning - A. Sanchez-Gonzalez (Nature Portfolio, 2017)
X-ray free-electron lasers, important light sources for materials research, suffer from shot-to-shot fluctuations that necessitate complex diagnostics. Here, the authors apply machine learning to accurately predict pulse properties, using parameters that can be acquired at high-repetition rates.